Numerical investigation on thermal hydraulic characteristics of steam jet condensation in subcooled water flow in pipes. (March 2022) - Xu, Qiang; Liang, Liang; She, Yonglu; Xie, Xiangdong; Guo, Liejin
Highlights: Steam jet condensation in subcooled water flow in pipes is studied numerically. A two-resistance model is applied for calculating interfacial heat and mass transfer. The total pressure peaks at the two-phase region's end due to water dynamic pressure. The expansion-contraction passage makes a steam jet accelerates to supersonic state. Heat transfer coefficients based on area and volume decrease as steam pressure rises. Abstract: Because of the high efficiency of heat and mass transfer, the direct contact condensation of the steam jet in subcooled water has been widely used in various industrial processes. Based on the previous experiments, this paper has established the numerical model and simulation method to describe the condensation of saturated steam discharging into the subcooled water in the pipe through the nozzle. Within the frame of the Euler-Euler two-fluid model, the heat and mass transfer in the condensation phase change of steam is calculated by the thermal phase-change model. When the steam pressure at the nozzle inlet increases from 150 kPa to 450 kPa, the steam plume gradually transforms from contraction cone to expansion-contraction cone. The length of the steam plume increases linearly from 0.59 de to 3.07 de . The condensation heat transfer coefficient based on the volume of the two-phase region gradually decreases from 4847.01 MW/m 3 K to 1988.16 MW/m 3 K. By analyzing the distribution of thermal-hydraulic parameters along the nozzle central axis, it is found that the expansion-contraction steam plume channel accelerates the steam jet to a supersonic state. The total pressure decreases suddenly at the nozzle outlet, and the water phase dynamic pressure causes the total pressure to rapidly increase to the maximum at the end of the gas-liquid two-phase region. When the steam pressure at the nozzle inlet is 450 kPa, the Ma number and maximum total pressure are up to 1.43 and 1228.2 kPa, respectively.